If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(y + 1) + -2x = 2 Reorder the terms: y(1 + y) + -2x = 2 (1 * y + y * y) + -2x = 2 (1y + y2) + -2x = 2 Reorder the terms: -2x + 1y + y2 = 2 Solving -2x + 1y + y2 = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -2x + 1y + -1y + y2 = 2 + -1y Combine like terms: 1y + -1y = 0 -2x + 0 + y2 = 2 + -1y -2x + y2 = 2 + -1y Add '-1y2' to each side of the equation. -2x + y2 + -1y2 = 2 + -1y + -1y2 Combine like terms: y2 + -1y2 = 0 -2x + 0 = 2 + -1y + -1y2 -2x = 2 + -1y + -1y2 Divide each side by '-2'. x = -1 + 0.5y + 0.5y2 Simplifying x = -1 + 0.5y + 0.5y2
| x-5/3-8=x-3/2 | | 10y=25y | | 2y+1-2x=2 | | 10+X=22 | | -4x+4y=2 | | 11x=19+41 | | 3y/10-3=4/5+4 | | 5/2d+2/5=65+95d | | 16x^2+28x+6= | | X+7=-100 | | -14=12y | | 5/2d+2/5=6/5+9/5d | | n/7=-8 | | X+7=100 | | x^3-4x^2-7x-10=0 | | Y=-3x^2+12x-21 | | -1=2u-3 | | -12+x=58 | | 8+(-16)= | | -2x+8=-55+7x | | x/7+x/4=11/28 | | -10w+6=-10 | | 25-(3-48)= | | 70-(3-48)= | | x+10=-6x-60 | | Y/3-10=-2 | | 0.2x+2y=1.6 | | 1/x+2/9x=-8 | | -16=14y | | 2(x+5)+y-10=180 | | 25-30y+9y^2=0 | | 5x/7-8=22 |